Evaluation of Kindergarten Group Rooms in the Context of Size Children and Teacher's Perspective in Turkey - Şahin, Belkıs Ece; DOSTOĞLU, NESLİHAN (My University, 2014)
Physical qualifications of group rooms are highly important in terms of child development during preschool education. First of all, the required space should be provided in order to create ideal conditions in a group room. The standards of the required space for a child in group rooms vary among countries. It is stated that in Turkey minimum 1.5 m2 space per child in group rooms is enough. This paper studies whether this standard rate, which is stated as insufficient according to various studies, is seen enough by the users; hence, 30 children and their teachers from three different kindergartens were interviewed. It is seen that the standards in Turkey which are considered as sufficient are actually not enough according to the comments of children and teachers. The purpose of this study is to present an example constructed on the idea that the standards should be defined according to the experiences of users, so to be able to reach the right solutions which meet the needs of users.
Keywords: Preschool education in Turkey; the minimum space requirement; changeability